DISPLACEMENT FIELDS AND MODELS OF CURRENT MOTION IN GORNY ALTAI - Timofeev V.Yu.; Ardyukov D.G.; Calais E.; Duchkov A.D.; Zapreeva E.A.; Kazantsev S.A.; Roosbeek F.; Bruyninx C. (My University, 2006)
We suggest a model of elastic rebound for the M = 7.3-7.5 Chuya earthquake of 27 September 2003 based on 3D deformation data from the Gorny Altai. We report processed data from yearly resurveyed Altai GPS stations through 2000-2004. The geodynamic network of the Institute of Geophysics (Novosibirsk) consists of 21 stations, including the Klyuchi reference station (world network code IGS-NVSK DOMES N12319 M001); it covers the structural elements of Gorny Altai and extends into the southern West Siberian plate and the West Sayan mountains. Displacement of the NVSK station in the system of permanent stations of Asia and displacement of Central Asian stations were processed to obtain a map of GPS velocities for the Gorny Altai. The velocities are in a range from 0.2 to 11 mm/yr. The velocity field shows signature of a preseismic process before the Chuya event in the southern Gorny Altai. Measurements through 2003-2004 give a pattern of postseismic deformation indicating a right-lateral strike slip in the epicentral area. The amount of displacement decreases away from the nodal plane from 300 mm at 15 km to 25 mm at 90 km far from the main shock. This regularity is explained in terms of elastic rebound in a 2D dislocation model. Modeling with the use of experimental data showed a 4MPa stress release and a 2 m displacement along the fault in the epicenter, at an average fault depth of 8 km. The shear strain related to the earthquake was estimated to be 10-6 within 100 km away from the rupture.
Keywords: VELOCITY FIELD; GPS GEODESY; ELASTIC REBOUND MODEL; CHUYA EARTHQUAKE OF 27.09.2003; GORNY ALTAI